Paciente de sexo femenino de 65 años de edad con cáncer de estómago. - Medina Lorenti, Nayla Yuleissy (2018)
Stomach cancer is a tumor that has a high prevalence of mortality worldwide and represents the fourth known and frequent cancer after cancer of the lung, breast, colon and rectum and is the third cause of death worldwide in both sexes. The term gastric cancer was first described by the French Bayle in 1883, gastric cancer is one that invades the submucosa with or without lymph node permission. Maintain an adequate nutritional status, to favor the functioning of the immune system The patient is an active smoker about 20 years ago, she is the daughter of a diabetic mother and a deceased father due to cancer of the liver. Go to the consultation for presenting heartburn for 10 days of evolution and reported bloody stools sporadically. The patient has his digestive tract in operation so it starts with a soft gastric diet that helps to appease the existing symptoms. This diet allows to modify dietary habits and decreases the production of gastric acids, significantly improving the signs and symptoms of this patient. This diet will be preserved during the stage of the disease, the control of these parameters was carried out every 15 days for 6 months, after which the control will be carried out once a month The nutritional status of the patient is improved through the anthropometric parameters, evidencing an increase in weight of 2kg in three months.